A Currency Crisis in Europe? The Europe's common currency and the new accession countries - Mariusz K. Krawczyk (Hamburg Institute of International Economics (HWWA), 2004)
The politically and legally complicated character of the EU Eastern Enlargement heavily influenced the conflict between the legal and economic rationality underlying the construction of the EMR-II. This makes the ERM-II vulnerable to currency crises and creates conditions for a widespread currency and asset substitution in the accession countries. As a result, the required participation of all accession countries in the ERM-II imposes unnecessary costs on the whole enlargement process. The costs could be avoided if the EU adopted a more flexible approach to the enlargement of its monetary union, allowing for an individual path of adopting the euro in each accession country depending on the country's economic conditions.
Keywords: F36; F33; F32; 330; EU enlargement; monetary integration; currency crisis; asset substitution; EU-Erweiterung; Europäischer Währungsverbund; Währungskrise; Europäische Wirtschafts- und Währungsunion; Europa